Comparative impact of different weight loss strategies on obstructive sleep apnea: an integrated review of surgical, pharmacological, and lifestyle interventions - Song, Guo-qiang; Hu, Guo-qiang (Frontiers in Neurology, 2025)
Obesity is recognized as one of the most significant risk factors for obstructive sleep apnea (OSA), and weight reduction remains an effective strategy for improving OSA symptoms. With the ongoing evolution of bariatric surgery, pharmacological therapies, and conventional weight management approaches such as dietary modification and exercise, there is growing interest in understanding the differential efficacy and mechanisms of these interventions for OSA management. This review systematically examines the impacts of surgical procedures (including bariatric surgeries like gastric sleeve), pharmacological treatments (such as GLP-1 receptor agonists, orlistat, and phentermine/topiramate), and lifestyle-based weight management on OSA outcomes. It analyzes the comparative effectiveness, underlying mechanisms, indications, and limitations of each approach, integrating insights from the latest clinical studies. Additionally, this review discusses the challenges and unresolved issues in the field, such as patient selection, long-term adherence, and the interplay between weight loss and OSA pathophysiology. The purpose of this article is to provide a comprehensive synthesis of current evidence, highlight gaps in knowledge, and outline future directions for integrating weight management strategies into the holistic care of patients with OSA.